Pengembangan Strategi Pemasaran Syariah Daging dan Ikan Halal melalui Digital Marketing :Studi Kasus Pada PT Daya Desa Asasta - Nurhasanah, Eva; Gusnadi, Dani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research is aimed at developing marketing strategies for halal meat and fish through digital marketing at PT Daya Desa Asasta. Digital marketing, or digital marketing, is a set of strategies to market goods or services through digital or online media, such as the Internet, social media, search engines, email, mobile applications, and other online platforms. This research assesses what has been implemented and which digital marketing strategies have had the most or the least impact. Through this research, more objective evaluations can be obtained, which can serve as the basis for making recommendations for improvements or decision-making related to marketing through digital marketing.This type of research is qualitative, using the research evaluation method and the goal-free evaluation model by Michael Scriven. Data collection is carried out with interviews with 2 subjects involved in the company's Power Village Asasta, observation, and document study. Data analysis with Miles & Huberman thematic analysis techniques (1994). Further, the monitoring of research credibility was carried out through steps of triangulation of data from Patton (1990). The results of the research were evaluation results, namely (a) 3 digital marketing strategies used: Tokopedia, Instagram, and Whatsapp (b) 1 digital marketing strategy and 1 recommended product processing.Keywords: Digital Marketing, Sharia Marketing, Meat ,and Fish